INDUSTRI KERAJINAN ANYAMAN OLAHAN PLASTIK BAPAK ALMUNIR DESA SETAIL KEC. GENTENG KAB. BANYUWANGI TAHUN1996-2022 - Habibatul Maula; Ahmad Arif Budiman Nasution; Bambang Soepeno; Jefri Rieski Triyanto (Jurnal Riset Multidisiplin Edukasi, 2026)
This study examines the development of the plastic woven handicraft industry owned by Mr. Almunir in Setail Village, Genteng District, Banyuwangi Regency from 1996 to 2022. The research is motivated by the sustainability of local craft industries that have survived for more than two decades amid globalization and modern industrial development. The objectives of this study are to identify the factors underlying the establishment of the industry and to analyze its development over time. This research employs a historical research method consisting of four stages: heuristics, source criticism, interpretation, and historiography. Data were collected through interviews, observations, documentation, and relevant literature. The findings indicate that the establishment of the industry was influenced by family economic needs, the owner’s weaving skills, and the availability of recycled plastic materials. The industry has developed through the modernization of production tools, increased production capacity reaching 450–500 units per month, and product diversification. In conclusion, the sustainability of this handicraft industry is supported by adaptability, product innovation, and the contribution of the local economic environment.